The Patient Protection and Affordable Care Act: The Impact on Urologic Cancer Care - Keegan, Kirk A. (2012)
In March 2010, the Patient Protection and Affordable Care Act as well as its amendments were signed into law. This sweeping legislation was aimed at controlling spiraling healthcare costs and redressing significant disparities in healthcare access and quality. Cancer diagnoses and their treatments constitute a large component of rising healthcare expenditures and, not surprisingly, the legislation will have a significant influence on cancer care in the United States. Because genitourinary malignancies represent an impressive 25% of all cancer diagnoses per year, this legislation could have a profound impact on urologic oncology. To this end, we will present key components of this landmark legislation, including the proposed expansion to Medicaid coverage, the projected role of Accountable Care Organizations, the expected creation of quality reporting systems, the formation of an independent Patient-Centered Outcomes Research Institute, and enhanced regulation on physician-owned practices. We will specifically address the anticipated effect of these changes on urological cancer care. Briefly, the legal ramifications and current barriers to the statutes will be examined.